Integração da disciplina de Sistemas Digitais na plataforma PmatE - Barbosa, Sérgio (2005)
This article approaches the process of integration of a Digital Systems course in the Mathematical Education Project platform, developed to support computer aided education. The paper describes how the project appeared and its scope, identifies the needed requirements needed before actual content production, describes the intrinsic procedures of the organization, development areas, used technologies and alsosome of the conceptual models of the information system. Several developed tools are presented and their main features are discussed in the framework of an undergraduate Digital Systems course.